1965
DOI: 10.1083/jcb.24.1.57
|View full text |Cite
|
Sign up to set email alerts
|

An Electron Microscope Study of the Development of a Mouse Hepatitis Virus in Tissue Culture Cells

Abstract: Samples taken at different intervals of time from suspension cultures of the NCTC 1469 line of mouse liver—derived (ML) cells infected with a mouse hepatitis virus have been studied with the electron microscope. The experiments revealed that the viruses are incorporated into the cells by viropexis within 1 hour after being added to the culture. An increasing number of particles are found later inside dense cytoplasmic corpuscles similar to lysosomes. In the cytoplasm of the cells from the samples taken 7 hours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
127
1
1

Year Published

1975
1975
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(141 citation statements)
references
References 54 publications
12
127
1
1
Order By: Relevance
“…The same SARS model demonstrated that viral replication occurs preferentially in circular structures known as convoluted membranes (Knoops et al, 2008) which may be precursors of DMVs. These structures were found to be identical to the 'reticular inclusions' first observed in cells infected with mouse hepatitis coronavirus (MHV) more than 40 years ago (David-Ferreira & Manaker, 1965) and subsequently referred to as 'clusters of tubular cisternal elements' (Krijnse-Locker et al, 1994). The small circular units observed in HCV RNA-replicating cells in our study (Fig.…”
Section: Discussionsupporting
confidence: 61%
“…The same SARS model demonstrated that viral replication occurs preferentially in circular structures known as convoluted membranes (Knoops et al, 2008) which may be precursors of DMVs. These structures were found to be identical to the 'reticular inclusions' first observed in cells infected with mouse hepatitis coronavirus (MHV) more than 40 years ago (David-Ferreira & Manaker, 1965) and subsequently referred to as 'clusters of tubular cisternal elements' (Krijnse-Locker et al, 1994). The small circular units observed in HCV RNA-replicating cells in our study (Fig.…”
Section: Discussionsupporting
confidence: 61%
“…Like HCV, both of them induce membranous replication complexes, and MHV replication complexes are associated with ER membranes (12). In contrast, Sindbis virus, another plus-strand RNA virus, which assembles replication complexes on membranes derived from lysosomes (21), is much less sensitive to BFA (reference 58 and our unpublished observation), suggesting that GBF1 is not required for its replication.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent to adsorption, the murine coronaviruses are presumably internalized into the host cell by absorptive endocytosis (David-Ferreira & Manaker, 1965). To examine the internalization of JHM by the various cell types, JHM-adsorbed cells were incubated at 37 °C for various time periods and the amount of virus internalized was determined as described in the legend to Fig.…”
Section: Virus Internalizationmentioning
confidence: 99%